Comprehensive evaluation of the MeltPro MTB/PZA assay for prediction of pyrazinamide resistance in multidrug-resistant tuberculosis - Guiqing He; Chunxia Tu; Yelei Zhu; Qingyong Zheng; Qiulong Zhou; Wenzhen Zhou; Ouyang Huang; Bin Chen; Zhengwei Liu; Ye Xu; Xiangao Jiang (Microbiology Spectrum)
ABSTRACT Resistance to pyrazinamide (PZA) poses significant challenges to tuberculosis (TB) management, and prediction of susceptibility to PZA has been challenging. This study examined PZA resistance-associated gene mutations in 125 multidrug-resistant clinical isolates of Mycobacterium tuberculosis (MTB) from Wenzhou, China. Phenotypic drug-susceptibility testing (pDST) for PZA was performed on clinical isolates using the MGIT 960 system to accurately determine resistance. Subsequently, whole-genome sequencing (WGS) was conducted on the 125 isolates to identify genetic mutations linked to PZA resistance, focusing specifically on the pncA, rpsA, and panD genes. To provide a rapid diagnostic alternative to traditional methods, the MeltPro MTB/PZA assay was also utilized to detect mutations in pncA. pDST revealed a PZA resistance rate of 59.20%, with 29.41% observed in strains resistant only to isoniazid and rifampicin, 77.61% in pre-extensively drug-resistant TB (pre-XDR-TB), and 100% in extensively drug-resistant TB (XDR-TB). Among the isolates, WGS identified mutations primarily in the pncA (64.00%) and rpsA (6.40%), with panD mutations not detected. PZA resistance was strongly associated with pncA mutations, present in 97.30% of PZA-resistant strains. WGS demonstrated 97.30% sensitivity and 84.31% specificity compared to pDST, while MeltPro MTB/PZA showed 91.89% sensitivity and 86.27% specificity. Compared to WGS, MeltPro MTB/PZA showed 92.50% positive percent agreement and 97.78% negative percentage agreement, highlighting its diagnostic value. In conclusion, PZA resistance in multidrug-resistant tuberculosis (MDR-TB) is primarily due to pncA mutations. MeltPro MTB/PZA assay offers a reliable, rapid alternative for PZA resistance prediction, supporting timely treatment adaptations for improved TB patient care.IMPORTANCEThis study underscores the pressing need for reliable diagnostic methods to address high PZA resistance rates in TB cases, particularly in MDR-TB strains. By confirming that pncA mutations are the principal drivers of PZA resistance, we highlight the diagnostic potential of the MeltPro MTB/PZA assay as a rapid and effective alternative to conventional culture-based methods. Demonstrating sensitivity and specificity comparable to WGS and pDST, this assay offers a practical, accessible approach for timely PZA resistance prediction. It supports more tailored and effective MDR-TB treatment strategies, which are essential for optimizing patient care in both well-resourced and constrained settings.